FIELD OBSERVATIONS REGARDING THE BIOLOGY OF OXYRHACHIS LEFROYI (HOMOPTERA: MEMBRACIDAE) - BHARATI, VIJAY; SHARMA, BALDEV (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Oxyrhachis Íefroyi is univoltine treehopper and observed in the field from February- March till December as per host preference, which during the extreme cold temperature hibernate under the bark or crevices of the host plant. Mating is preceded after precopulatory pairing (PCP), which is observed mostly during morning and before noon as compared to evening when few PCPs are noticed. Eggs are laid in ovipositional slits, which are arranged in palmate manner between bark and underlying cortex.